2020
DOI: 10.3389/fonc.2020.01036
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Therapeutic Predictive, and Prognostic Value of Neutrophil Extracellular Traps in Patients With Gastric Adenocarcinoma

Abstract: Neutrophils are a significant population of infiltrated immune cells in the tumor microenvironment. Neutrophil extracellular traps (NETs) are implicated in the biological behavior of many malignant tumors. NETs can be degraded into soluble nucleosomes, leading to the release of fragments containing DNA and granule proteins into the peripheral blood (PB). Using human gastric cancer (GC) biopsies and PB samples, we investigated the specific value of NETs in GC from a clinical perspective. In summary, the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…Previous reports on single parameter staining indicated that the abundance of NETs in lymphoma as well as pancreatic and ovarian cancer, correlates with worse overall prognosis [19–21]. Mouse data are supportive of pathogenic mechanisms exerted by NETs, but this remains unresolved in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on single parameter staining indicated that the abundance of NETs in lymphoma as well as pancreatic and ovarian cancer, correlates with worse overall prognosis [19–21]. Mouse data are supportive of pathogenic mechanisms exerted by NETs, but this remains unresolved in humans.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell lymphoma patients show increased circulating levels of NETs that correlate with serum IL-8 and worse prognosis [19]. Moreover, reports suggest the presence of NETs in pancreatic, gastric, and ovarian cancer where they correlate with worse prognosis [20][21][22][23]. However, accurate analytical studies supporting reliable measurement of NETs are needed [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, elevated NET levels, measured as serum MPO-DNA molecules, correlates with metastatic phenotype of colorectal cancer patients [27]. Moreover, the levels of circulating NE-DNA complexes increased with the stage of the disease in breast and gastric cancers [28,29]. Increased levels of plasma biomarkers of activated neutrophils and NETs, such as cfDNA, NE and citH3, have also recently been detected in a mouse model of pancreatic cancer [30].…”
Section: Nets In Cancer As Diagnostic and Predictive Useful Biomarkersmentioning
confidence: 99%
“…High neutrophil infiltration is associated with breast cancer aggressiveness and therapy resistance mediated by pro-tumor neutrophil characteristics due to the cancer cell-neutrophil interactions [39]. Tumor cells release cytokines and chemokines such as IL-8, IL-17 and G-CSF, CXCL5 and CXCL6 [18,40] that attract neutrophils from the bone marrow to tumor sites [29,39,41,42]. It has been demonstrated that significant neutrophil heterogeneity exists.…”
Section: Intratumoral Nets and Netosis In Cancer Progressionmentioning
confidence: 99%
“…In gastric cancer (GC), the analysis of blood samples has revealed higher levels of NETs in patients with benign gastric disease than healthy controls [ 69 ]. The results indicate a better diagnostic value of NETs than carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9).…”
Section: Nets In Cancer Progression and Metastasismentioning
confidence: 99%